Perché l’anti-scienza ha successo? - Fuso, Silvano (Chimica nella Scuola, 2024)
A worrying anti-scientific attitude is quite widespread in our society. The recent coronavirus pandemic has highlighted this well. Analyzing and understanding the causes of this phenomenon is surely the first step in trying to counter it.